Nutritional requirements of ticks. - Perner, Jan (Jihočeská univerzita, 2017)
Ticks acquire nutrients only by a parasitic nature of feeding on animals, including humans. During this process, a wide array of pathogens is transmitted. Ticks of the Ixodidae family receive exactly one blood meal in each active developmental. Knowing the trophic dependence of tick metabolism on the host blood meal components may enable discovering processes essential for the tick physiology and development. Exploiting a membrane system of tick feeding and whole blood fractionation, we have revealed that adult ticks need to acquire host haemoglobin-derived haem so that they can produce viable larvae, and reproduce. Haem is not further catabolised in ticks, and iron is thus acquired via independent route with the host serum transferrin as a source molecule. Using RNA-seq, we compared transcriptome compositions between guts of blood- and serum-fed ticks. We identified fifteen gut transcripts that change their levels with respect to the presence/absence of dietary red blood cells. Glutathione S-transferase, one of the identified encoded molecules, shows a clear haeminresponsive expression at both transcript and protein levels. Its apparent haem-binding properties suggest that this protein is directly involved in haem homeostasis maintenance within the tick gut. The ultimate goal of such research is to identify and verify targets that, when blocked, would render the acquisition and/or distribution system of haem in ticks nonfunctional. This would represent a novel way of anti-tick interventions in veterinary and human medicine.
Nutritional requirements of ticks.
Keywords: tick; haem; iron; RNAi; vaccine; glutathione S-transferase; auxotrophy; tick; haem; iron; RNAi; vaccine; glutathione S-transferase; auxotrophy